Ankylosing Spondylitis Patients Display Aberrant ERAP1 Gene DNA Methylation and Expression. (18th August 2022) - Ma, Yubo; Fan, Dazhi; Xu, Shanshan; Deng, Jixiang; Gao, Xing; Guan, Shiyang; Zhang, Xu; Pan, Faming
ABSTRACT: Background: Endoplasmic reticulum aminopeptidase 1 (ERAP1) is known to participate in the pathogenesis of ankylosing spondylitis (AS). This study aimed to evaluate the relationship between promoter methylation and mRNA levels of ERAP1 and AS susceptibility. Methods: DNA methylation levels of 100 AS patients and 100 healthy controls (HCs) were tested using a targeted bisulfite sequencing assay. To verify the results of DNA methylation, mRNA levels of ERAP1 were measured in 20 AS patients and HCs used quantitative real-time reverse transcription-polymerase chain reaction. Results: The DNA methylation levels of two CpG islands containing 31 loci in ERAP1 promoter were measured. ERAP1_1 ( P < .001) and ERAP1_2 ( P < .001) islands were significantly hypermethylated in AS patients compared with HCs. In the verification study, the mRNA levels of ERAP1 were significantly decreased in AS patients. The ROC curve analysis showed that the sensitivity, specificity and area under curve were 0.717, 0.737, and 0.779 of differential methylated CpG loci of ERAP1 for AS diagnosis. In AS patients, the methylation levels of EARP1 were associated with family history, non-steroidal anti-inflammatory drugs use, X-ray classification, and clinical manifestations. Conclusions: Our study demonstrated that the ERAP1 gene is significantly hypermethylated, and mRNA levels of EARP1 decreased, in AS patients. Our findings suggested that the aberrant methylation of ERAP1 promoter may be involved in the pathogenesis of AS and could be considered as a diagnostic tool and therapeutic target of AS. Abbreviations AS: Ankylosing Spondylitis; AUC: Area Under Curve; BASDAI: Bath Ankylosing Spondylitis Disease Activity Index; BASFI: Bath Ankylosing Spondylitis Functional Index; CI: Confidence Interval; CpG: Cytosine-guanine Dinucleotide; CRP: C-reactive Protein; ERAP1: Endoplasmic Reticulum Aminopeptidase 1; ESR: Erythrocyte Sedimentation Rate; EWAS: Epigenome-Wide Association Study; HLA: Human Leukocyte Antigen; OR: Odds Ratio; PCR: Polymerase Chain Reaction; ROC: Receiver Operating Characteristic; NSAIDs: Non-Steroidal Anti-Inflammatory Drugs.